An Ecological Study of Tuberculosis Incidence in China, From 2002 to 2018 - Zhang, Qianyun; Song, Wanmei; Liu, Siqi; An, Qiqi; Tao, Ningning; Zhu, Xuehan; Yang, Dongmei; Wan, Daoxia; Li, Yifan; Li, Huaichen (Frontiers in Public Health, 2022)
Introduction: Tuberculosis is one of the main infectious diseases threatening global health, which is also the main cause of death from a single source of infection (above HIV/AIDS). China is a country with a high burden of tuberculosis in the world, ranking only behind India and Indonesia. However, there are few ecological studies on the burden of tuberculosis in China. This study aims to provide more research basis for the government to formulate tuberculosis policies by conducting an ecological study of tuberculosis burden in China, so as to achieve the goal of eliminating tuberculosis by 2030. Methods: We collected data on the incidence of tuberculosis and ecological factors of 31 provinces, autonomous regions, and municipalities in Mainland China (excluding Taiwan, Hong Kong, and Macau) from 2002 to 2018. We conduct a comprehensive index system of ecological factors affecting the incidence, which consists of 5 secondary indicators and 35 tertiary indicators., and construct a dynamic panel data model based on the Lasso Regression to select variables to test the effect of each ecological factor on the incidence. Results: Among the 35 tertiary indicators, economy 3,4,6,7, environment 1, recourses 1,3 , demography 3, and lifecare 2,4,8,9,13 passed the significance test at the 1% level, economy 1,2,5, environment 2,9, lifecare 6,12 passed the significance test at the 5% level, lifecare 10 passed the significance test at the 10% level. Only economy 5 and economy 6 are positively have a positive impact on the incidence, and the other statistically significant ecological indicators are negatively correlated with the incidence. Conclusions: Our study indicated that many ecological factors, including residents' income, unemployment rate, educational level, medical resources, population density, sunshine duration and dietary structure, are closely related to the incidence of tuberculosis. These findings contribute to taking targeted measures for tuberculosis prevention and control.